1994
DOI: 10.1002/1097-4679(199407)50:4<578::aid-jclp2270500413>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of MMPI and MMPI-2 in PTSD assessment

Abstract: A sample of 47 Vietnam veterans with the diagnosis of combat‐related Post‐Traumatic Stress Disorder (PTSD) was administered the MMPI and MMPI‐2. Pairwise comparisons were performed on the clinical scales, Harris Lingoes subscales, and scales relevant to the assessment of PTSD. Correlational analyses were performed as well. Hit rates of high‐point pairs were compared across the tests. The results suggest a high degree of congruence between tests. Differences were seen on evaluations of some scales between tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The sample as a whole was relatively small, yet still closely comparable to other recent studies of PTSD (Albrecht et al, 1994;Hyer et al, 1987;Wilson & Walker, 1990). However, in actual practice, the clinician at a juvenile justice facility typically is faced with a similar dilemma.…”
Section: Evaluating Ptsd With the Mmpi-asupporting
confidence: 63%
See 1 more Smart Citation
“…The sample as a whole was relatively small, yet still closely comparable to other recent studies of PTSD (Albrecht et al, 1994;Hyer et al, 1987;Wilson & Walker, 1990). However, in actual practice, the clinician at a juvenile justice facility typically is faced with a similar dilemma.…”
Section: Evaluating Ptsd With the Mmpi-asupporting
confidence: 63%
“…Thus, it has been referred to as a "trauma profile" (Wilson & Walker, 1990). Recent studies with the MMPI and MMPI-2 (Butcher, Dahlstrom, Graham, Tellegen, & Kaemer, 1989) have suggested that the PK scale is a valid, reliable measure (Albrecht et al, 1994, Litz et al, 1991. The PK scale consists of 49 items that were found to best discriminate groups of Vietnam veteran psychiatric patients diagnosed with and without combatrelated PTSD.…”
mentioning
confidence: 99%
“…Results indicate no significant differences among the personality profiles of the three trauma-exposed groups. A normative NEO-PI profile for persons diagnosed with combat-related PTSD is presented, characterized by an extremely high Neuroticism score (T>75) and an extremely low Agreeableness score (T<25).Psychological assessments of Vietnam veterans with post-traumatic stress disorder (PTSD) generally have focused on measurement of personality psychopathology and common profiles, primarily through the use of the MMPI and MMPI-2 (Albrecht et al., 1991;Hyer et al, 1986;Hyer et al, 1988;Talbert et al, 1991;Watson, 1990), and on measurement of PTSD symptomatology through a variety of specially designed combat-related PTSD instruments and scales (i.e.…”
mentioning
confidence: 99%
“…Psychological assessments of Vietnam veterans with post-traumatic stress disorder (PTSD) generally have focused on measurement of personality psychopathology and common profiles, primarily through the use of the MMPI and MMPI-2 (Albrecht et al, 1991; Hyer et al, 1986; Hyer et al, 1988; Talbert et al, 1991; Watson, 1990), and on measurement of PTSD symptomatology through a variety of specially designed combat-related PTSD instruments and scales (i.e., Mississippi Scale for Combat-related PTSD, Keane, Caddell, & Taylor, 1988; MMPI PTSD subscale, Keane, Malloy, & Fairbank, 1984). Little research has explored personality dimensions of combat veterans using measures of normal personality designed to assess enduring traits (Hyer, Gratton, & Melton, in press;Wiggins & Pincus, 1989).…”
mentioning
confidence: 99%
“…Studies in Vietnam veterans that used the successor to the MMPI, the MMPI-2, have shown that the mean score on Scale 7 (Psychasthenia; Pt) is often slightly higher than the score on Scale 2 (D; Albrecht et al, 1994;Baldrachi, Hilsenroth, Arsenault, Sloan, & Walter, 1999;Forbes, Creamer, & McHugh, 1999;Litz et al, 1991;Wetter, Baer, Berry, Robinson, & Sumpter, 1993;Weyermann, Norris, & Hyer, 1996). This suggests that the mean MMPI-2 profile for trauma-related pathology in combat veterans may be best characterized as an 87/78 code type with Scale 2 (D) following closely, also described as an 872 code type.…”
mentioning
confidence: 99%